Efforts To Improve Social Sciences Learning Outcomes Indonesian Cultural Diversity Material Through The Numbered Heads Together (NHT) Collaborative Learning Model For Fourth-Grade Students Of SDN Baran - Utami, Prihma Sinta; Kusumadewi, Friska Nur; Saptiningsih, Tutik (Universitas Negeri Malang, 2024)
Hasil capaian dalam pelajaran IPS khususnya pada siswa kelas 4 SD N Baran masih rendah. Tujuan penelitian ini adalah untuk mendeskripsikan peningkatan hasil belajar IPS melalui pembelajaran kooperatif tipe NHT pada siswa kelas 4 SD N Baran. Penelitian ini merupakan Penelitian Tindakan Kelas. Objek penelitian adalah siswa kelas 4 SD N Baran yang berjumlah 9 orang. Pendekatan penelitian menggunakan pendekatan kualitatif. Metode tes dan non tes berupa observasi digunakan sebagai metode pengumpulan data. Metode analisis data yang digunakan adalah metode kuantitatif dan kualitatif. Penelitian dilaksanakan dalam 2 siklus. Hasil penelitian menunjukkan bahwa rata-rata nilai tes meningkat setiap siklusnya. Pada pra tindakan hasil rata-rata 51,79 meningkat menjadi 12,30 menjadi 64 pada siklus I, dan pada siklus II mean 81 meningkat 17. Pada pra tindakan mencapai 0% meningkat 11% menjadi 22 % pada Siklus I. Pada Siklus II ketuntasan meningkat sebesar 67%, sehingga pencapaian ketuntasan siswa pada Siklus II mencapai 89%. Artinya hasil belajar IPS meningkat dari Siklus I hingga akhir Siklus II. Dapat dikatakan bahwa penerapan model pembelajaran kooperatif tipe NHT dapat meningkatkan hasil belajar siswa. The learning achievement in Social Studies, particularly among Grade 4 students at SD N Baran, is still low. The purpose of this study is to describe the improvement in Social Studies learning outcomes through the cooperative learning model of the NHT (Numbered Heads Together) type among Grade 4 students at SD N Baran. This research is a Classroom Action Research. The subject of the research was 9 students in Grade 4 at SD N Baran. The research used a qualitative approach. Data collection methods included both test and non-test techniques, such as observation. The data analysis methods used were quantitative and qualitative. The study was conducted in two cycles. The results showed that the average test score increased in each cycle. In the pre-action stage, the average score was 51.79, which increased by 12.30 points to 64 in Cycle I, and further rose to 81 in Cycle II with an improvement of 17 points. In the pre-action stage, 0% of students achieved mastery; this increased by 11% to 22% in Cycle I. In Cycle II, mastery increased by 67%, so that student mastery in Cycle II reached 89%. This indicates that Social Studies learning outcomes improved from Cycle I to the end of Cycle II. It can be concluded that the application of the cooperative learning model of the NHT type can improve student learning outcomes.